Intramuscular Chondroid Lipoma: Magnetic Resonance Imaging Diagnosis by ‘Fat Ring Sign’ - Yıldız, Adalet Elçin (Balkan Med J, 2015)
BACKGROUND: Chondroid lipoma is an extremely rare variant of benign lipomatous lesions that is composed of lipoblasts, mature fat, and chondroid matrix. Although benign lipomatous lesions are the most common soft tissue tumors and imaging findings are often pathognomonic, there have been few reports describing the imaging features of chondroid lipoma. CASE REPORT: We present magnetic resonance imaging (MRI) findings of a pelvic intramuscular chondroid lipoma in a 59 year-old man and describe a “fat ring sign” that may be useful to diagnose this rare tumor radiologically. CONCLUSION: Magnetic resonance imaging findings of a chondroid lipoma may be heterogenous according to the distribution of the fatty and chondroid tissue. However, in the presence of “fat ring sign,” radiologists should consider a diagnosis of chondroid lipoma preoperatively.